Correlations between core muscle strength endurance and upper-extremity performance in adolescent male sub-elite handball players - Bauer, Julian; Gruber, Markus; Muehlbauer, Thomas (Frontiers in Sports and Active Living, 2022)
Handball is an Olympic contact sport with high physical, tactical, and technical demands by the players. Out of the different techniques, throwing is the most important one to be able to score. The objective of the study was to investigate the relationships between core muscle strength endurance (Bourban test: ventral, dorsal and lateral chain) and shoulder mobility/stability (Upper Quarter Y Balance test [YBT-UQ]) as well as throwing velocity in adolescent male sub-elite handball players (N = 32, age: 17.1 ± 0.7 years, height: 181.8 ± 6.3 cm, BMI: 24.6 ± 4.9 kg/m2). All participants were free of injuries at least two weeks prior to the study, experienced (training experience: 8.5 ± 3.3 years) handball players who were tested mid-season in the evening of one of their training sessions. Pearson correlations were calculated for core muscle strength endurance with (a) shoulder mobility/stability and (b) throwing velocity. The throwing arm reach displayed significant correlations (both p < 0.05) between the Bourban test (ventral chain) and the inferolateral reach direction (IL) of the YBT-UQ (r = 0.41) as well as the composite score (CS) (r = 0.34). For the dorsal chain, significant correlations (all p < 0.01) were found for the medial (MD) (r = 0.42) and IL (r = 0.61) reach direction as well as the CS (r = 0.51). For the right but not the left side of the lateral chain, significant correlations (both p < 0.05) were detected for the IL reach direction (r = 0.40) and the CS (r = 0.35). For the non-throwing arm reach, significant correlations were found between the ventral chain and the MD reach direction (r = 0.53, p < 0.01) as well as the CS (r = 0.31, p < 0.05). For the dorsal chain, significant correlations (all p < 0.01) were found for the MD (r = 0.47) and IL (r = 0.44) reach direction as well as the CS (r = 0.41). For the lateral chain, significant correlations were detected for the MD (left and right side: r = 0.49, p < 0.01) and IL (left and right side: r = 0.35, p < 0.05) reach direction as well as the CS (left and right side: r = 0.37, p < 0.05). The dorsal chain but not the ventral and lateral chain of the Bourban test showed a significant correlation with throwing velocity (r = 0.33, p < 0.05). Our results indicate that better core muscle strength endurance is associated with better shoulder mobility/stability as well as partially higher throwing velocity of adolescent male sub-elite handball players. Therefore, practitioners should integrate core muscle strength endurance exercises into the training routines to improve upper-extremity performance of this target group.